Influence of multiple daily injections of oxytocin on reproductive and milk characteristics of postpartum dairy cows - R.E. Stewart; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1986)
Release of oxytocin at the time of suckling or milking may delay onset of estrous cycles in postpartum cows. Twenty lactating Holsteins were used in this study to determine if multiple daily injections of oxytocin would prolong postpartum anestrus. Cows received either oxytocin or saline (controls) intravenously through indwelling jugular catheters four times daily for 28 days following calving. Treatment with oxytocin did not lengthen intervals to ovulation or estrus or alter secretion patterns of luteinizing hormone, cortisol, progesterone, or 13,14-dihydro-15-keto prostaglandin F2αin serum. Although milk production, percentage protein, and somatic cell counts were similar between treatment groups, oxytocin appeared to increase (P<.10) percentage of fat 0.99 vs 3.68%) in milk. Involution of the reproductive tract (uterus and cervix) was also similar between oxytocin-treated and control cows. We concluded that oxytocin alone does not prevent the occurrence of estrus and ovulation in dairy cows or hasten the rate of cervical and uterine involution.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Oxytocin; Reproductive; Postpartum